2021
DOI: 10.1126/sciadv.abj0611
|View full text |Cite
|
Sign up to set email alerts
|

Novel suction-based in vivo cutaneous DNA transfection platform

Abstract: Suction-mediated cutaneous DNA uptake yielded high in vivo efficiency and thus provides an alternative transfection platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 36 publications
0
47
1
Order By: Relevance
“…The application of suction to the skin has been found to increase vasodilation and blood flow to the application site and to cause tensile stresses that may stimulate recruitment of immune cells, both of which would be expected to contribute to better immunogenicity after ID vaccine delivery (57,58). Design, modeling, and optimization of the GeneDerm suction devise was recently described (32). In this prior study, application of suction to rat skin with GeneDerm was atraumatic by histologic exam and induced gene expression within an hour after injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of suction to the skin has been found to increase vasodilation and blood flow to the application site and to cause tensile stresses that may stimulate recruitment of immune cells, both of which would be expected to contribute to better immunogenicity after ID vaccine delivery (57,58). Design, modeling, and optimization of the GeneDerm suction devise was recently described (32). In this prior study, application of suction to rat skin with GeneDerm was atraumatic by histologic exam and induced gene expression within an hour after injection.…”
Section: Discussionmentioning
confidence: 99%
“…In anticipation of future clinical investigation of pGO-1002, we moved to investigate pGO-1002 immunogenicity after intradermal (ID) vaccination as this route is more accessible and more tolerable than intramuscular injection. In a recent study, we developed a new ID delivery protocol for DNA plasmids that involves the application of suction to the ID injection site which they found led to more rapid and robust transgene expression in rat skin (32). Furthermore, they demonstrated that ID immunization with a DNA vaccine followed by suction applied by our GeneDerm device led to more rapid and stronger antibody responses in rats.…”
Section: Genederm-assisted Intradermal Immunization Of Rats With Pgo-...mentioning
confidence: 99%
See 1 more Smart Citation
“…[157] Very recently, Lallow et al drew inspiration from traditional therapies used in China and the Middle East to develop a noninvasive and effective approach that utilizes suction to facilitate DNA delivery. [158] After intradermal Mantoux injection of plasmid DNA into rat skin, the injection site is subjected to a moderate negative pressure, which can enhance the transfection efficacy and immune response without causing significant tissue damage. This technology is cost-effective, easy to implement and does not require substantial training, which may have broad application in the future.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Suction devices that stretch the skin using hypobaric pressure have been developed to improve burn therapy ( 19 ), wound healing ( 20 ), skin laser therapy ( 21 ), and the in vivo transfection of DNA after intradermal injection ( 22 ). The safety of skin stretching using suction has been well-established using these devices and it has been extensively studied as a means to determine skin elasticity; for example, the Cutometer, a commercial hypobaric system that uses 500 mbar of pressure to measure skin elasticity in humans, has been reported in >200 studies.…”
mentioning
confidence: 99%